Low-dose valine attenuates diet-induced metabolic dysfunction-associated steatotic liver disease (MASLD) in mice by enhancing leptin sensitivity and modulating the gut microbiome - Felicianna; Emily K.K. Lo; Congjia Chen; Marsena J. Ismaiah; Fangfei Zhang; Hoi Kit Matthew Leung; Hani El-Nezami (Elsevier, 2024)
Objectives: Elevated circulating branched-chain amino acids (BCAAs) have been associated with obesity, insulin resistance, and MASLD. Nonetheless, BCAA supplementation has been shown to provide protective outcomes towards the intervention of MASLD. Currently, there is a lack of study towards the contribution of the BCAA: valine on MASLD. Herein, the effect of low-dose valine supplementation was investigated for its role in the progression of MASLD. Methods: C57BL/6J mice were fed a high-fat/high-cholesterol diet (HFD) to induce MASLD. Upon the establishment of MASLD, valine was supplemented via voluntary oral administration. Clinical and biochemical parameters associated with MASLD were measured, and molecular mechanism and gut microbiota modulation from the effect of valine were investigated. Results: Low-dose valine was found to attenuate the progression of MASLD, significantly reducing the gain in body weight, liver weight, and epididymal white adipose tissue (eWAT) weight, while also attenuating hyperglycemia and hyperleptinemia, and improving serum lipid profiles. Mechanistically, in the liver, genes related to hepatic lipogenesis and cholesterol biosynthesis were downregulated, while those associated with fatty acid oxidation, autophagy, and antioxidant capacity were upregulated, and AMPK pathway activity was enhanced. Liver and hypothalamic leptin resistance and inflammation were also attenuated, allowing better appetite control in mice fed a HFD and leading to reduced food intake. Additionally, metabolic flexibility in the eWAT was improved, and the gut microbiome was modulated by low-dose valine supplementation. Conclusion: Low-dose valine supplementation attenuates MASLD by enhancing systemic leptin sensitivity and modulating the gut microbiome.